Complex association between alanine aminotransferase activity and mortality in general population: a systematic review and meta-analysis of prospective studies. - Zhengtao Liu; Huaijun Ning; Shuping Que; Linlin Wang; Xue Qin; Tao Peng (PLoS ONE)
Objective Controversy exists in using alanine aminotransferase (ALT) activity for predicting long-term survival. Therefore, this research study investigated the association between ALT activity and mortality through a systematic review and meta-analysis of previous prospective studies. Methods Electronic literature databases, including PubMed, Embase, and the Institute for Scientific Information (ISI), were searched for relevant prospective observational studies (published before Dec 30, 2013) on the association between baseline ALT activity and ensuing all-cause/disease-specific mortality. Information on nationality, sample size, participant characteristics, follow-up duration, comparison, outcome assessment, hazard ratios (HRs) and adjusted covariates was extracted. Pooled HRs and corresponding 95% confidence intervals (CIs) were separately calculated for categorical risk estimates (highest vs. lowest ALT categories) and continuous risk estimates (per 5 U/l of ALT increment) in subgroups separated by age (<70/≥ 70 years). Results A total of twelve prospective cohort studies, totaling 206,678 participants and 16,249 deaths, were identified and analyzed. In the younger age group, the pooled HR for mortality related to liver-disease was about 1.24 (95% CI: 1.23-1.25) per 5 U/l of ALT increment. The dose-response HRs of all-cause mortality, cardiovascular (CV) disease-related mortality, and cancer-related mortality were 0.91 (0.88-0.94), 0.91 (0.85-0.96), 0.92 (0.86-0.98) respectively per 5 U/l of ALT elevation, with insignificant heterogeneity in the older population. There was an approximate decrease of 4‰ observed on HRs of all-cause, CV-related, and cancer-related mortality followed with one year's increment through meta-regression (all P<0.05). Conclusions The ALT-mortality association was inconsistent and seems particularly susceptible to age after synthesizing the previous prospective studies. In terms of the age, ALT activity was more valuable in predicting mortality in the older population; extremely low ALT levels indicated a higher all-cause, CV-related, and cancer-related mortality. ALT activity may therefore be a useful biomarker when predicting the long-term survival of elderly patients.